2019
DOI: 10.1186/s13054-019-2662-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventilation in patients with acute ischaemic stroke: from pathophysiology to clinical practice

Abstract: Most patients with ischaemic stroke are managed on the ward or in specialty stroke units, but a significant number requires higher-acuity care and, consequently, admission to the intensive care unit. Mechanical ventilation is frequently performed in these patients due to swallowing dysfunction and airway or respiratory system compromise. Experimental studies have focused on stroke-induced immunosuppression and brain-lung crosstalk, leading to increased pulmonary damage and inflammation, as well as reduced alve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 85 publications
(133 reference statements)
1
72
0
7
Order By: Relevance
“…The majority of sedative drugs can cause hypotension, which might negatively affect cerebral blood flow in the critical time period after recanalization, possibly influencing final infarct size. Additionally, hyperoxaemia may be present for a longer time in patients with delayed extubation, which might contribute to secondary brain injury and worse outcomes [15,16]. Furthermore, early diagnostic stroke workup may be impeded in patients who remain intubated for a longer time, potentially leading to delays in specific treatment of stroke causes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of sedative drugs can cause hypotension, which might negatively affect cerebral blood flow in the critical time period after recanalization, possibly influencing final infarct size. Additionally, hyperoxaemia may be present for a longer time in patients with delayed extubation, which might contribute to secondary brain injury and worse outcomes [15,16]. Furthermore, early diagnostic stroke workup may be impeded in patients who remain intubated for a longer time, potentially leading to delays in specific treatment of stroke causes.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients had an M1-segment occlusion of the middle cerebral artery (65.3%); 58.6% had been treated with intravenous thrombolysis before MT. Median National Institutes of Health Stroke Scale (NIHSS) at admission was 15 (interquartile range [11][12][13][14][15][16][17][18] and successful recanalization (thrombolysis in cerebral infarction grades 2b-3) was achieved in 88.5% of the patients (Table 1).…”
Section: Patient Characteristics and Outcomementioning
confidence: 99%
“…Battaglini D; Bonatti G; Robba C; Rocco PRM; Pelosi P Dear Editor, We thank Professor Bilotta and colleagues for their interest in our recent scientific contribution [1]. The authors pointed out the role of neuroinflammation due to mechanical ventilation in stroke, thus advising the relevance of possible novel pharmacological strategies.…”
Section: Authors' Responsementioning
confidence: 99%
“…
read with great attention and interest the review by Robba and colleagues on mechanical ventilation (MV) in patients with acute ischemic stroke [1].The authors examined the pathophysiology of stroke and the risk for pulmonary complications (brain-lung "dangerous" crosstalk, immunological response after stroke, stroke-associated pneumonia, and dysphagia) then concluding with useful recommendations on optimal ventilator settings and therapeutic strategies.Several preclinical evidence supports that MV correlates with neuroinflammation and cognitive dysfunction [2,3].Surprisingly the authors in their review cite a paper from Hegeman and colleagues that challenge the hypothesis of the relationship between MV and brain inflammation state: "In the brain, MV did not induce a significant change in adhesion molecule mRNA expression as compared with non-ventilated controls, […] did not induce a detectable cytokine or chemokine response, [...] myeloperoxidase activity was below detection level in all experimental groups" [4].Of interest, the study from Klinger and colleagues reported evidence on the effect of intravenous lidocaine on the transcerebral inflammatory response during cardiac surgery [5]. In their randomized controlled clinical trial, the authors aimed to investigate the potential antineuroinflammatory effect of intravenous lidocaine and observed "a reduction in the transcerebral activation of platelet-monocyte conjugates after aortic cross-clamp release.
…”
mentioning
confidence: 99%
See 1 more Smart Citation